Analisis Pengaruh Orientasi Kewirausahaan, Inovasi, dan Kapabilitas Pemasaran terhadap Keunggulan Bersaing pada UKM Olahan Ikan di Semarang - Lisda Rahmasari (STIE Widya Manggala, 2021)
This study aimed to find out the influence of entrepreneurial orientation, innovation and marketing capabilities on competitive advantage. The research population comprised Fish Processing Business in Semarang City. The sample was selected by means of the purposive sampling technique. The sample was 100 companies. The data were collected by a questionnaire, interviews, and documentation. This research uses Structural Equation Modeling (SEM) analysis technique using AMOS 24.0 analysis tool. The test results using Structural Equation Modeling (SEM) analysis techniques indicate that the model is in accordance with population data. The results of the study showed that entrepreneurship oriented , innovation and marketing capabilities had a significant positive effect on competitive advantage. Used by analyzer for example validity test, test reliabilitas, and hipotesis test use modelling equation structural (SEM).